2020
DOI: 10.20463/pan.2020.0011
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing breast cancer by exercise: consideration to animal models and exercise protocols

Abstract: Exercise is thought to have a significant effect on chemotherapy, and previous studies have reported that exercise can increase patient survival. Thus, in this review, we aimed to summarize various animal models to analyze the effects of exercise on breast cancer. [Methods] We summarized types of breast cancer animal models from various reports and analyzed the effects of exercise on anti-cancer factors in breast cancer animal models. [Results] This review aimed to systematically investigate if exercise could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Preclinical studies on breast cancer analyzing the isolated effect of each therapy, as proposed in this study, are well explored in the literature; however, there is still a wide variation in therapeutic parameters, such as the type and time of exercise [ 91 ], the dose, the route and type of omega-3 [ 43 , 54 ], and the MHT parameters (temperature, time, magnetic field, and oscillation frequency), as well as the type of magnetic nanoparticle used [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies on breast cancer analyzing the isolated effect of each therapy, as proposed in this study, are well explored in the literature; however, there is still a wide variation in therapeutic parameters, such as the type and time of exercise [ 91 ], the dose, the route and type of omega-3 [ 43 , 54 ], and the MHT parameters (temperature, time, magnetic field, and oscillation frequency), as well as the type of magnetic nanoparticle used [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that mice bearing mammary tumors that had access to running wheels displayed diminished growth in both MCF-7 and MDA-MB-231 tumors [ 94 , 95 , 96 ]. In a prior study of ours, alterations in urinary proteins were observed by collecting samples from mice subjected to 5 min tibia loading, as well as from human individuals before and after a 30 min session of step aerobics.…”
Section: Effects Of Physical Activitiesmentioning
confidence: 99%